Microzonation of ground dominant periods at city of Ensenada, Baja California - Ibarra-Torúa, Gema; López-Pineda, Leobardo; Acosta-Chang, José (Revista de la Construcción. Journal of Construction, 2015)
The civil structures are mostly damaged when the fundamental period of the structure is close to the dominant period of ground motion (DP) where it is founded. To increase the security of the seismic design of new structures or the reinforcement of existing structures, it is essential to develop microzonation maps of the dominant period, where urban spots and areas with high potential for future urban development will contain. We presented a map with the distribution of DP of soils in the city of Ensenada, Baja California, México, using the method of spectral ratios with ambient vibration, obtaining consistent results, either by the distribution of lithology and like previous studies in other areas, as presented values are within the ranges published in other works in different areas at world. Importantly, this work is part of a project, in which DP were measured in four urban centers of the state of Baja California, México.